White-Box Testing Framework for Object-Oriented Programming based on Message Sequence Specification - Rodríguez Silva, Juan Ignacio (2018)
Software is a crucial element in the functionality of devices and industry. Likewise, the operation of an enterprise or organization depends largely on the reliability of the software systems used for supporting the business process or particular tasks. The quality of software has become the most important factor in determining the success of products or enterprises. In order to accomplish a quality software product several methodologies, techniques, and frameworks have been developed, each of them tailored to specific areas or characteristics of the software under review. This paper presents a white-box testing framework for Object- Oriented Programming based on Message Sequence Specification. In the context of an object-oriented program, our framework can be used to test the correct order in which the methods of a class are invoked by its clients. The implementation of the framework is based on aspect-oriented programming.